Factors’ learning motivation dynamics in training course: a study with students in Kazakhstan - Omarova, Maral K.; Mirza, Natalya V. (Frontiers in Education, 2025)
The article demonstrates the relevance of the presented topic, draws attention to the problem of low learning motivation among students, poor quality study of training courses, and the need to consider the dynamics of learning motivation among students during their development. The purpose of the study is to identify the factors that influence the dynamics of students’ learning motivation at various phases of training course, and then to modify the course’s structure accordingly. Students were surveyed using two questionnaires created by the authors: “Learning motivation” and “Dynamics of learning motivation.” Participating in the survey were students from university and college. Students identified the dynamics of learning motivation for several course components. Organizational, psychological, communicative, target and effective are the factors of dynamics of learning motivation. The analysis enabled the identification of the factors influencing the dynamics of students’ learning motivation, which must be incorporated into the course’s instructional design.